Maltrato psicológico infantil y su influencia en el comportamiento de los estudiantes del 5 año de E.G.B de la Escuela San José del cantón Babahoyo de la Provincia de Los Ríos - Fernández Casis, Maoly Liseth (2019)
The study of the case reveals that since our ancestors saw how violence fueled violence, children have been victims of violence beyond their lives after death. Today, their behavior is exercised quietly at home, on the street at school and has become a common and socially accepted practice. Children's centers become a privileged place to face the problem, since all children experience it and the teacher is the active agent that most relates to children, allowing them to observe and know the child's behavior in class your companions. Interpersonal relationships are in crisis, characterized by dependence and rejection. This is reflected in the indifference of parents and teachers, so that the child can become very dependent on the signs of affection, constantly exposing himself to danger, sexual abuse and rejection. There is also a weak tendency in the relationship between the degree of affectivity between parents and children, which constitutes a serious problem of relationship and adaptation in society. Psychological abuse affects all levels of growth and development of the child, communication through a sincere dialogue between teachers, parents and children so that all citizens make significant changes in their lives, as does the current government. Children will improve and may be less problematic, since the acquired behaviors are a reflection of a deteriorated society that has passed from generation to generation without reaching a solution due to lack of knowledge and total disinterest that never stopped